ENTREPRENEURSHIP ADDENDUMS ON HOFSTEDE’S DIMENSIONS OF NATIONAL CULTURE - Bojadjiev, Marjan; Mileva, Ivona; Tomovska Misoska, Ana; Vaneva, Marjana (The European Journal of Applied Economics, 2023)
Hofstede’s definition (2001) of national culture - that it is mental programming: a pattern of thoughts, feelings, and actions that each person acquires in childhood and then applies throughout life – arms us with an ability to explain the differences in attitudes towards work. In his model, which consists of six dimensions, Hofstede describes the society’s culture effect on values. As national culture is deeply rooted in the society’s norms and shapes the individual’s behavior, it very strongly molds the entrepreneurial spirit in one country. Namely, a society that wants to promote entrepreneurship and the emergence of more entrepreneurs definitely needs culture that supports it. The paper introduces fear of failure as a seventh dimension and high staus to entrepreneurs as an eighth dimension to Hofstede’s six-dimensional model of national culture and looks closely into countries’ differences by analyzing the impact that the dimensions have on the determination of that country’s population to start a business.By studying the secondary data from the Global Entrepreneurship Monitor, eight economies have been desk-researched.
Keywords: national culture; hofstede dimensions; fear of failure; high status to entrepreneurs